IMPORTANCE-SATISFACTION ANALYSIS OF RAIL SERVICES IN THE UK WITH RESPECT TOTRAVEL TIME USE - Yosritzal, Yosritzal; Dissanayake, Dilum; Bell, Margaret (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
The availability of information and communication technology such as Wi-Fi and electric socket on-board is expected to change consumer attitude and behaviour toward rail services as time spent travelling could be more productive and enjoyable. However, do the availability of Wi-Fi and electric power socket on-board were more importance than other performance attributes in consumers’ perception? This paper presents the result of an importance-satisfaction analysis of several attributes of train services in the UK. The study found that ticket price; reliability and seating guarantee were more importance than other attributes whilst Wi-Fi and electric socket were less importance. The results indicated that travel time use is just a complementary of the main objective of travel, which is to arrive at the destination.